Impacto do Bolsa Família e do Benefício de Prestação Continuada na pobreza e na desigualdade no nordeste do Brasil nos anos de 2016 e 2019 - Fernandes, Mirian Raquel Do Nascimento (2022)
This research aims to investigate the effects of the Bolsa Família (BF) and Benefício de Prestação Continuada (BPC) programs on poverty and inequality in the Northeast region of Brazil. The research is characterized as descriptive with a quantitative approach. The microdata used were extracted from the Continuous National Household Sample Survey (PNADC) for the years 2016 and 2019. To calculate poverty, the Foster, Greer and Thorbecke (FGT) indicators were used; the calculation of the level of inequality in the region was performed using the Gini index; and to assess the impact of the BF and BPC programs in the region, the Propensity Score Matching (PSM) method was adopted. As for the profile of the beneficiaries of the programs, the results point out that for both programs in the two years studied, most of the beneficiaries are female, of brown color, low level of education, out of the workforce (BPC) and in the workforce. work (BF) and residents of the urban area. The average age among BF beneficiaries was around 37 years old (for both years). Regarding the BPC, the average age for the years 2016 and 2019 were respectively 48 and 50 years old. In 2016, 41,8% of Northeasterners were poor and 12.8% were extremely poor, proportions that in 2019 became 39,6% poor and 13,7% extremely poor. Between 2016 and 2019, there was an increase in inequality in the region from 0,556 to 0,569. In 2016, the state with the highest inequality index in the region was Pernambuco (0,579). In 2019, the highest Gini index was identified in Sergipe (0,591). Regarding the impacts generated by the programs, the results indicate that Bolsa Família was able to reduce extreme poverty in 2016. In turn, the value of the BPC was able to reduce the condition of poverty. It was also verified that both programs exert positive effects in reducing poverty and income inequality in the Northeast region.